Integrating augmented reality technology into physical therapy in the school setting: a feasibility study - Elise Baron; Amy Pratt; Betsy Donahoe-Fillmore (Annals of Medicine)
Purpose To determine the feasibility of using an immersive augmented-reality technology (AT) in conjunction with physical therapy (PT) for in-school therapy, while determining whether this technology would be as engaging and motivating as standard PT.Methods Participants included Fifteen students (6–8 y/o) receiving once-weekly PT. The therapist was instructed to engage students in AT and standard PT for one academic year, alternating sessions. Before each session, students were informed of therapy modality and rated their excitement using a Smiley Face Likert scale with associated text. To assess feasibility, the number and order of each session type, as well as student refusal rate, were investigated. To assess engagement, the therapist recorded time-on-task and number of times redirection was needed. Feasibility was reported as descriptive statistics, and Wilcoxon signed-rank tests were used to compare average scores on excitement and engagement between AT and standard PT.Results 60% of students (9/15) reaching the intended goal of 50% of therapy sessions as AT, as well as 60% (9/15) of students ‘roughly alternating’ (no more than three same session types in a row) their sessions throughout the duration of the study. The student refusal rate of AT was 0%. When using AT, students were 23% (p= <.0001) more excited, 4.4% (p=.004) more on task and needed 61% (p= <.0001) less refocusing compared to standard PT.Conclusion Integrating AT alongside standard PT proved to be moderately feasible in a school setting. Additionally, students demonstrated increased excitement, increased time on tasks and decreased refocusing during a session using AT. A flexible-use approach will make AT a motivating addition to school-based therapy.